Applying a Positive (Organizational) Psychology Lens to the Study of Employee Green Behavior: A Systematic Review and Research Agenda - Meyers, Maria Christina; Rutjens, Demi (Frontiers in Psychology, 2022)
Employees can play a decisive role in combatting climate change by engaging in green behavior at work. Research on employee green behavior has recently gained traction, with research results pointing to the considerable influence of positive variables (e.g., personal values, positive affect) on employee green behavior. While such positive variables lie at the heart of the scholarly discipline positive organizational psychology, there is scant research at the intersection of positive organizational psychology and employee green behavior. The current manuscript aims to give impetus to such research. To this end, the manuscript presents a systematic review of the literature on positive predictors of employee green behavior and identified 94 articles that investigate such predictors. We explicitly map these investigated predictors onto a positive (organizational) psychology frame of reference. Subsequently, we use the findings of the review to identify gaps and outline concrete suggestions for future research at the intersection of positive organizational psychology and employee green behavior, addressing both theoretical and methodological suggestions.